Empowering Business Resilience: The Impact of Inclusive Leadership and Organizational Adaptability through Open Innovation - Pride Lambe, Kristian Hoegh; Cheriani, Cheriani (Integrated Journal of Business and Economics (IJBE), 2025)
This study examines the effects of inclusive leadership and organizational adaptation on business resilience in Makassar City's hotel business using through the perspective of open innovation. This study applies a quantitative approach, examining data from 96 hotel managers adopting the Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings of the study show that open innovation has a impact on business resilience, while the direct effect of inclusive leadership and organizational adaptability on business resilience is not significant. However, through open innovation, both show significant useful effect. This study underlines the importance of external collaboration, technology adoption, and innovation implementation in increasing business resilience. These results are relevant for the business approach in the era of disruption, especially in the context of the hospitality industry in Indonesia. This study shows that open innovation, such as collaborating with outside partners, adopting new technology, and encouraging fresh ideas, is key to helping hotels in Makassar become more resilient in times of disruption. While inclusive leadership and adaptability alone do not directly improve resilience, they do have a strong positive effect when combined with open innovation. This means hotel managers should focus on creating a culture that supports teamwork, openness, and learning from others outside the organization. For policymakers, the findings suggest the need to support innovation networks and provide training or resources that help hotels connect with external experts and stay competitive. This approach is especially important in the fast-changing hospitality industry in Indonesia